Perancangan Sistem Kontrol Kecepatan Motor DC Dengan PID Labview 2010 - Fauzy Fauzy; Sugiatmo Kasmungin (Manutech : Jurnal Teknologi Manufaktur, 2017)
The stability of the system is the main objective for Control System Design criteria. PID control with closed loop system is the one of control which can improve the stability of the system from disturbance effect. In this study, DC Motor Speed Control is designed with PID LabVIEW 2010 Software and Proximity Sensor as a closed loop feedback. The system allows the operator to control speed of DC Motor from LabVIEW front panel which automatically stabilized when load ?which usually slow down the speed of DC Motor, applied. PID LabVIEW 2010 generates voltage output 0-5Vdc and drives DC Motor through analog output channel from NIDAQ 600, which received by Non-Inverting Amplifier and amplified to 0-12Vdc output. PID Control with Closed Loop system may dampen the speed response second order of DC Motor to have value of overshoot number ? 0 with steady state error of ?2%. The system feedback can stabilize this condition from outside interference. The result of this speed control system has success criteria of overshoot (Mp) = 0 and Error Steady State (Ess) = 0.82%.